2010
DOI: 10.3748/wjg.v16.i27.3427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of type 2 diabetes in Algerian patients with hepatitis C virus infection

Abstract: The high prevalence of diabetes in HCV-infected patients, and its occurrence at early stages of hepatic disease, suggest that screening for glucose abnormalities should be indicated in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 22 publications
2
34
3
3
Order By: Relevance
“…The overall prevalence of HCV infection in the general population in our study is found to be 1.58% and was lower than the prevalence reports from close countries; Algeria (2.5%), Libya (3%) and Egypt (15%-20%) [10-12]. Our estimate was also too much lower compared to what has been reported in the prior decade by Cacoub et al [13] in which the estimated HCV infection rate was 7.7%.…”
Section: Discussioncontrasting
confidence: 78%
“…The overall prevalence of HCV infection in the general population in our study is found to be 1.58% and was lower than the prevalence reports from close countries; Algeria (2.5%), Libya (3%) and Egypt (15%-20%) [10-12]. Our estimate was also too much lower compared to what has been reported in the prior decade by Cacoub et al [13] in which the estimated HCV infection rate was 7.7%.…”
Section: Discussioncontrasting
confidence: 78%
“…In another study, IR in nondiabetic individuals was not independently associated with HCV infection after adjustment for ALT and GGT elevation, whereas ALT and GGT elevation were independent predictors . In a third study, both HCV infection and ALT elevation were independently associated with diabetes . A decreased incidence of diabetes after successful treatment of HCV (sustained virological response; SVR) has also been reported .…”
Section: Discussionmentioning
confidence: 91%
“…The probable role could be due to induction of insulin resistance through destruction of insulin signaling pathways associated with overproduction of proinflammatory cytokines, such as IL-6 and TNF-α, in response to HCV infection and direct and/or indirect immune-mediated cytopathic effects of HCV on pancreatic islet cells, which may result in the destruction of β-cells and subsequently reduced insulin production [4, 21-23]. Insulin resistance presents at the early stages of chronic HCV infectioin, even prior to progression to fibrosis and cirrhosis [21, 22]. …”
Section: Discussionmentioning
confidence: 99%